Polymer composite capacitor electrode material and method for preparing the same

CN123017744APending Publication Date: 2026-10-30SHENZHEN LIRON ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610896861.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明在制备聚合物复合电容器电极材料时,将尿素、柠檬酸三钠、六水合硝酸铈和过氧化氢反应制得空心纳米氧化铈;将空心纳米氧化铈与吡咯、吡咯-3-羧酸聚合制得氧化铈-共聚聚吡咯核壳纳米球,再与高锰酸钾反应制得分级多孔核壳微球;将分级多孔核壳微球与共聚聚吡咯涂覆于预处理碳布制得中间体电极;将中间体电极浸入1,2-二(2-溴乙基)二硫交联剂溶液反应形成交联网络结构,制得聚合物复合电容器电极材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1782109305829-000001
    Figure REF-OBJ-1782109305829-000001
  • Figure REF-OBJ-1782109305829-000003
    Figure REF-OBJ-1782109305829-000003
Patent Text Reader

Abstract

The application discloses a kind of polymer composite capacitor electrode materials and preparation method thereof, it is related to capacitor electrode material technical field.The application when preparing polymer composite capacitor electrode material, urea, trisodium citrate, cerium nitrate hexahydrate and hydrogen peroxide are reacted to obtain hollow nanometer cerium oxide;Hollow nanometer cerium oxide is polymerized with pyrrole, pyrrole-3-carboxylic acid to obtain cerium oxide-copolymer polypyrrole core-shell nanosphere, and then reacted with potassium permanganate to obtain hierarchical porous core-shell microspheres;Hierarchical porous core-shell microspheres and copolymer polypyrrole are coated on pretreated carbon cloth to obtain intermediate electrode;The intermediate electrode is immersed in 1,2-di (2-bromoethyl) dithio crosslinking agent solution to form crosslinked network structure, and polymer composite capacitor electrode material is prepared.The electrode material prepared by the application effectively enhances mechanical integrity and interface stability through crosslinked structure, has high specific capacitance, excellent cycle stability and UV aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of capacitor electrode materials technology, specifically to a polymer composite capacitor electrode material and its preparation method. Background Technology

[0002] Supercapacitors, as high-power energy storage devices, are in urgent demand in fields such as start-stop systems for new energy vehicles and emergency power supplies. Their performance hinges on the electrode materials. While pseudocapacitive materials, represented by conductive polymers (such as polypyrrole) and metal oxides, can provide high specific capacitance, they generally suffer from inherent defects: polypyrrole experiences severe volume expansion during charge and discharge, leading to poor cycle stability; most metal oxides have poor conductivity, limiting rate performance; and simple physical composites are prone to problems such as poor interfacial contact, low utilization of active materials, and numerous "dead zones," making it difficult to achieve breakthroughs in the overall electrochemical performance of these materials.

[0003] To address these issues, researchers often employ nanostructure design and composite strategies. For example, constructing core-shell structures or introducing porous frameworks to buffer volume changes. However, traditional methods are often complex, requiring templates or harsh etchants, and struggle to precisely control shell thickness and pore distribution, leading to insufficient structural stability. Another approach is to improve conductivity through chemical doping or surface modification; however, most modification steps are cumbersome, dopant distribution is uneven, and active sites are prone to failure during long-term cycling. Furthermore, existing methods often sacrifice mechanical strength or interfacial compatibility while improving specific capacity, making it difficult to balance overall electrode cycle life and power characteristics. Therefore, developing a novel polymer-based electrode material synthesis technology that simultaneously achieves controllable structural fabrication, uniform component composite, and a mild and environmentally friendly process is crucial for advancing high-performance supercapacitors. Summary of the Invention

[0004] The purpose of this invention is to provide a polymer composite capacitor electrode material and its preparation method to solve the problems existing in the prior art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A polymer composite capacitor electrode material is prepared by coating a mixture of hierarchical porous core-shell microspheres and copolymerized polypyrrole onto pretreated carbon cloth and then crosslinking the mixture.

[0006] As an optimization, the hierarchical porous core-shell microspheres are prepared by polymerizing hollow cerium oxide nanoparticles with pyrrole and pyrrole-3-carboxylic acid to obtain cerium oxide-copolymer polypyrrole core-shell nanospheres, and then reacting them with potassium permanganate.

[0007] As an optimization, the copolymerized polypyrrole is prepared by copolymerizing pyrrole and pyrrole-3-carboxylic acid in anhydrous acetonitrile with ferric chloride hexahydrate as an oxidant.

[0008] As an optimization, the crosslinking is achieved by impregnating the coated electrode with a methanol solution of 1,2-bis(2-bromoethyl)disulfide.

[0009] A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:(75~79):(1~1.2):(2.5~3):(160~170). Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 5~15 min. Add cerium nitrate hexahydrate and continue to react for 15~25 min. Add hydrogen peroxide and continue to react for 20~40 min to obtain a mixed solution. Heat the mixed solution to 95~105℃ and maintain for 1.5~2.5 h. Transfer to a high-pressure reactor and maintain at 175~185℃ for 15~20 h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid and deionized water are mixed at a mass ratio of 1:(2.3~2.5):(3.9~4.1):(120~130) and ultrasonically treated at 100~300W for 25~35min to obtain a mixed suspension; 1.2~1.3 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid ferric chloride hexahydrate is weighed and dissolved in 1M methanesulfonic acid aqueous solution at 16wt%~20wt% to obtain an oxidizing agent solution; the oxidizing agent solution is added dropwise to the mixed suspension at 0~5℃. After the addition is complete, the mixture is ultrasonically treated at 25~30℃ at 80~120W for 5~7h, filtered, washed with deionized water and ethanol, and dried. Cerium oxide-copolymerized polypyrrole core-shell nanospheres were prepared. Cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate were weighed at a mass ratio of 1:(0.7~0.8). The cerium oxide-copolymerized polypyrrole core-shell nanospheres were added to deionized water at a concentration of 0.5wt%~1.5wt%, and the mixture was ultrasonically treated at 100~300W for 25~35min to obtain a suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres. The suspension was stirred at 65~70℃ for 5~10min, and 1wt%~2wt% potassium permanganate aqueous solution was added dropwise. After the addition was complete, the reaction continued for 1.5~2.5h. The mixture was centrifuged, washed with deionized water and anhydrous ethanol, and freeze-dried to obtain fractionated porous core-shell microspheres. (3) Mix pyrrole and pyrrole-3-carboxylic acid at a molar ratio of 1:(0.8~1) to obtain a mixed monomer; weigh 1.2~1.3 times the total molar amount of ferric chloride hexahydrate, dissolve ferric chloride hexahydrate in anhydrous acetonitrile at 16wt%~20wt% to obtain oxidant solution 2; dissolve the mixed monomer in anhydrous acetonitrile at 10wt%~20wt%, add oxidant solution 2 dropwise at 0~5℃, and continue the reaction for 12~24h after the addition is complete, precipitate in ice water, wash with anhydrous acetonitrile and deionized water, dry, and obtain copolymer polypyrrole; (4) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 1wt%~3wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:(0.23~0.27):(1.9~2.4), grind for 15~20min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 70~90℃ for 1~3h, and vacuum dry at 55~65℃ for 8~10h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 25~30℃ for 5~7min, take it out and rinse with methanol and deionized water, and vacuum dry at 55~65℃ for 11~13h to obtain a polymer composite capacitor electrode material.

[0010] As an optimization, the hollow nano-cerium oxide in step (1) has an average diameter of 324±32nm and a wall thickness of 62±8nm.

[0011] As an optimization, the pretreatment method for the pretreated carbon cloth in step (4) is as follows: 65% nitric acid and 95% sulfuric acid are mixed evenly at a volume ratio of 1:2 to obtain a mixed acid; potassium permanganate is dissolved in the mixed acid at 4wt%~4.5wt% to obtain an oxidizing solution; the carbon cloth is immersed in the oxidizing solution and reacted at 25~35℃ for 5~7h; 3~4 times the volume of deionized water is added to the oxidizing solution and the reaction continues for 2.5~3.5h; 2~3 drops of 33% hydrogen peroxide solution are added and the reaction continues for 10~20min; the carbon cloth is taken out, washed with deionized water and anhydrous ethanol, and dried to obtain the pretreated carbon cloth.

[0012] As an optimization, the carbon cloth model is W0S1011, and the manufacturer is Taiwan Carbon Energy Technology Co., Ltd.

[0013] As an optimization, the reaction after immersion in the crosslinking agent solution in step (4) is as follows: .

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: In preparing the polymer composite capacitor electrode material, the present invention reacts urea, trisodium citrate, cerium nitrate hexahydrate, and hydrogen peroxide to obtain hollow cerium oxide nanoparticles; polymerizes the hollow cerium oxide nanoparticles with pyrrole and pyrrole-3-carboxylic acid to obtain cerium oxide-copolymer polypyrrole core-shell nanospheres, and then reacts them with potassium permanganate to obtain hierarchical porous core-shell microspheres; coats the hierarchical porous core-shell microspheres and copolymer polypyrrole onto pretreated carbon cloth to obtain an intermediate electrode; immerses the intermediate electrode in a 1,2-bis(2-bromoethyl)disulfide crosslinking agent solution to form a crosslinked network structure, thereby obtaining the polymer composite capacitor electrode material.

[0015] First, hollow cerium oxide nanoparticles synthesized via a hydrothermal method were used as the structural unit. Their thin-walled, hollow nature provided pseudocapacitance while significantly improving the material's specific capacitance and shortening the plasma diffusion distance. A uniform conductive polymer shell was formed by in-situ polymerization of pyrrole and pyrrole-3-carboxylic acid on its surface. This shell not only constructed a three-dimensional electron conduction network, but the introduced carboxyl functional groups also enhanced the hydrophilicity of the material surface. Subsequently, oxidation treatment with potassium permanganate was used to grow highly active manganese oxide nanoflowers in situ on the core-shell structure surface, while simultaneously etching to create hierarchical channels. This process greatly increased the contact interface between the electrode and the electrolyte, forming a coherent ion transport channel composed of macropores, mesopores, and manganese oxide nano-interstices, thereby simultaneously improving the material's specific capacitance, rate performance, and active material utilization.

[0016] Secondly, by constructing a dynamically stable internal electrode structure, the capacity decay problem of polymer electrodes during long-term cycling was specifically addressed. The copolymer polypyrrole molecular chains, acting as conductive binders, are covalently linked by a crosslinking agent containing dynamic disulfide bonds, forming a three-dimensional network that runs through the entire active coating. This network tightly binds the core-shell microspheres and other active material particles, strongly adhering them to the carbon cloth current collector. Its core advantage lies in the reversible breaking and recombination characteristics of the disulfide bonds in the crosslinking bridges, which can enhance the electrode's electronic and ionic conductivity and effectively dissipate the periodic stress generated by ion insertion / extraction during charging and discharging, thereby buffering the structural volume changes of the active material and inhibiting the pulverization and peeling of the electrode material. Furthermore, the known anti-UV aging properties of the cerium oxide core component also provide additional long-term stability assurance for the electrode in applications involving light exposure. Ultimately, these mechanisms work together to enable the composite electrode to achieve high energy density while exhibiting excellent power characteristics and cycle life. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] To more clearly illustrate the method provided by the present invention, the following embodiments will be described in detail.

[0019] Example 1:

[0020] A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:75:1:2.5:160. Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 5~15min. Add cerium nitrate hexahydrate and continue to react for 15min. Add hydrogen peroxide and continue to react for 20min to obtain a mixed solution. Heat the mixed solution to 95℃ and keep it for 1.5h. Transfer it to a high-pressure reactor and keep it at 175℃ for 15h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid and deionized water were mixed in a mass ratio of 1:2.3:3.9:120 and ultrasonically treated at 100W for 25 min to obtain a mixed suspension; ferric chloride hexahydrate was weighed in an amount equal to 1.2 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid, and ferric chloride hexahydrate was dissolved in 1M methanesulfonic acid aqueous solution at 16wt% to obtain an oxidizing agent solution; the oxidizing agent solution was added dropwise to the mixed suspension at 0℃, and after the addition was complete, the mixture was ultrasonically treated at 25℃ at 80W for 5 h, filtered, washed with deionized water and ethanol, and dried to obtain cerium oxide. - Copolymerized polypyrrole core-shell nanospheres; Weigh cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate at a mass ratio of 1:0.7. Add 0.5wt% of cerium oxide-copolymerized polypyrrole core-shell nanospheres to deionized water and sonicate at 100W for 25min to obtain a cerium oxide-copolymerized polypyrrole core-shell nanosphere suspension. Stir the cerium oxide-copolymerized polypyrrole core-shell nanosphere suspension at 65℃ for 5min, add 1wt% potassium permanganate aqueous solution dropwise, and continue the reaction for 1.5h after the addition is complete. Centrifuge, wash with deionized water and anhydrous ethanol, freeze dry, and prepare fractionated porous core-shell microspheres. (3) Pyrrole and pyrrole-3-carboxylic acid were mixed at a molar ratio of 1:0.8 to obtain a mixed monomer; 1.2 times the total molar amount of ferric chloride hexahydrate was weighed, and ferric chloride hexahydrate was dissolved in anhydrous acetonitrile at 16 wt% to obtain oxidant solution 2; the mixed monomer was dissolved in anhydrous acetonitrile at 10 wt%, and oxidant solution 2 was added dropwise at 0℃. After the addition was completed, the reaction was continued for 12 h. The precipitate was collected in ice water, washed with anhydrous acetonitrile and deionized water, and dried to obtain copolymer polypyrrole. (4) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 1 wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.23:1.9 and grind for 15 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 70℃ for 1 h, and vacuum dry at 55℃ for 8 h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 25℃ for 5 min, take it out and rinse with methanol and deionized water, and vacuum dry at 55℃ for 11 h to obtain a polymer composite capacitor electrode material.

[0021] Example 2:

[0022] A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:77:1.1:2.8:165. Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 10 min. Add cerium nitrate hexahydrate and continue to react for 20 min. Add hydrogen peroxide and continue to react for 30 min to obtain a mixed solution. Heat the mixed solution to 100℃ and keep it for 2 h. Transfer it to a high-pressure reactor and keep it at 180℃ for 17 h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid, and deionized water were mixed in a mass ratio of 1:2.4:4:125 and ultrasonically treated at 200W for 30 min to obtain a mixed suspension. Ferric chloride hexahydrate was weighed in a mass ratio of 1.25 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid. Ferric chloride hexahydrate was dissolved in 1M methanesulfonic acid aqueous solution at 18wt% to obtain an oxidizing agent solution. The oxidizing agent solution was added dropwise to the mixed suspension at 3℃. After the addition was complete, the mixture was ultrasonically treated at 27℃ at 100W for 6 h. The mixture was then filtered, washed with deionized water and ethanol, and dried to obtain the oxidizing agent. Cerium-copolymerized polypyrrole core-shell nanospheres: Cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate were weighed at a mass ratio of 1:0.76. The cerium oxide-copolymerized polypyrrole core-shell nanospheres were added to deionized water at 1 wt%, and the mixture was sonicated at 200 W for 30 min to obtain a suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres. The suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres was stirred at 67 °C for 8 min, and 1.5 wt% potassium permanganate aqueous solution was added dropwise. After the addition was completed, the reaction was continued for 2 h. The mixture was centrifuged, washed with deionized water and anhydrous ethanol, and freeze-dried to prepare fractionated porous core-shell microspheres. (3) Pyrrole and pyrrole-3-carboxylic acid were mixed in a molar ratio of 1:0.9 to obtain a mixed monomer; 1.25 times the total molar amount of ferric chloride hexahydrate was weighed, and ferric chloride hexahydrate was dissolved in anhydrous acetonitrile at 18 wt% to obtain oxidant solution 2; the mixed monomer was dissolved in anhydrous acetonitrile at 15 wt%, and oxidant solution 2 was added dropwise at 3℃. After the addition was completed, the reaction was continued for 18 h. The precipitate was collected in ice water, washed with anhydrous acetonitrile and deionized water, and dried to obtain copolymer polypyrrole. (4) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 2wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.25:2.2 and grind for 17 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 80℃ for 2 h, and vacuum dry at 60℃ for 9 h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 27℃ for 6 min, take it out and rinse with methanol and deionized water, and vacuum dry at 60℃ for 12 h to obtain a polymer composite capacitor electrode material.

[0023] Example 3:

[0024] A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:79:1.2:3:170. Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 15min. Add cerium nitrate hexahydrate and continue to react for 25min. Add hydrogen peroxide and continue to react for 40min to obtain a mixed solution. Heat the mixed solution to 105℃ and maintain for 2.5h. Transfer to a high-pressure reactor and maintain at 185℃ for 20h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid and deionized water were mixed at a mass ratio of 1:2.5:4.1:130 and ultrasonically treated at 300W for 35 min to obtain a mixed suspension; ferric chloride hexahydrate was weighed in an amount equal to 1.3 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid, and ferric chloride hexahydrate was dissolved in 1M methanesulfonic acid aqueous solution at 20wt% to obtain an oxidizing agent solution; the oxidizing agent solution was added dropwise to the mixed suspension at 5℃, and after the addition was complete, the mixture was ultrasonically treated at 30℃ at 120W for 7 h, filtered, washed with deionized water and ethanol, and dried to obtain cerium oxide. - Copolymerized polypyrrole core-shell nanospheres; Weigh cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate at a mass ratio of 1:0.8. Add 1.5wt% of cerium oxide-copolymerized polypyrrole core-shell nanospheres to deionized water and sonicate at 300W for 35min to obtain a cerium oxide-copolymerized polypyrrole core-shell nanosphere suspension. Stir the cerium oxide-copolymerized polypyrrole core-shell nanosphere suspension at 70℃ for 10min, add 2wt% potassium permanganate aqueous solution dropwise, and continue the reaction for 2.5h after the addition is complete. Centrifuge, wash with deionized water and anhydrous ethanol, freeze dry, and prepare fractionated porous core-shell microspheres. (3) Mix pyrrole and pyrrole-3-carboxylic acid at a molar ratio of 1:1 to obtain a mixed monomer; weigh 1.3 times the total molar amount of ferric chloride hexahydrate, dissolve ferric chloride hexahydrate in anhydrous acetonitrile at 20 wt% to obtain oxidant solution 2; dissolve the mixed monomer in anhydrous acetonitrile at 20 wt%, add oxidant solution 2 dropwise at 5℃, continue the reaction for 24 h after the addition is complete, precipitate in ice water, wash with anhydrous acetonitrile and deionized water, dry, and obtain copolymer polypyrrole; (4) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 3 wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.27:2.4 and grind for 20 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 90℃ for 3 h, and vacuum dry at 65℃ for 10 h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 30℃ for 7 min, take it out and rinse with methanol and deionized water, and vacuum dry at 65℃ for 13 h to obtain a polymer composite capacitor electrode material.

[0025] Comparative Example 1: A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid and deionized water were mixed in a mass ratio of 1:2.4:4:125 and ultrasonically treated at 200W for 30 min to obtain a mixed suspension; ferric chloride hexahydrate was weighed in a mass ratio of 1.25 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid, and ferric chloride hexahydrate was dissolved in 1M methanesulfonic acid aqueous solution at 18wt% to obtain an oxidizing agent solution; the oxidizing agent solution was added dropwise to the mixed suspension at 3℃, and after the addition was complete, the mixture was ultrasonically treated at 27℃ at 100W for 6 h, filtered, washed with deionized water and ethanol, and dried to obtain cerium oxide. - Copolymerized polypyrrole core-shell nanospheres; Weigh cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate at a mass ratio of 1:0.76. Add 1 wt% of cerium oxide-copolymerized polypyrrole core-shell nanospheres to deionized water and sonicate at 200 W for 30 min to obtain a cerium oxide-copolymerized polypyrrole core-shell nanosphere suspension. Stir the cerium oxide-copolymerized polypyrrole core-shell nanosphere suspension at 67 °C for 8 min, add 1.5 wt% potassium permanganate aqueous solution dropwise, and continue the reaction for 2 h after the addition is complete. Centrifuge, wash with deionized water and anhydrous ethanol, freeze dry, and prepare fractionated porous core-shell microspheres. (2) Pyrrole and pyrrole-3-carboxylic acid were mixed in a molar ratio of 1:0.9 to obtain a mixed monomer; 1.25 times the total molar amount of ferric chloride hexahydrate was weighed, and ferric chloride hexahydrate was dissolved in anhydrous acetonitrile at 18 wt% to obtain oxidant solution 2; the mixed monomer was dissolved in anhydrous acetonitrile at 15 wt%, and oxidant solution 2 was added dropwise at 3℃. After the addition was completed, the reaction was continued for 18 h. The precipitate was collected in ice water, washed with anhydrous acetonitrile and deionized water, and dried to obtain copolymer polypyrrole. (3) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 2wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.25:2.2 and grind for 17 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 80℃ for 2 h, and vacuum dry at 60℃ for 9 h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 27℃ for 6 min, take it out and rinse with methanol and deionized water, and vacuum dry at 60℃ for 12 h to obtain a polymer composite capacitor electrode material.

[0026] Comparative Example 2: A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:77:1.1:2.8:165. Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 10 min. Add cerium nitrate hexahydrate and continue to react for 20 min. Add hydrogen peroxide and continue to react for 30 min to obtain a mixed solution. Heat the mixed solution to 100℃ and keep it for 2 h. Transfer it to a high-pressure reactor and keep it at 180℃ for 17 h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid and deionized water were mixed in a mass ratio of 1:2.4:4:125 and ultrasonically treated at 200W for 30min to obtain a mixed suspension; ferric chloride hexahydrate was weighed in 1.25 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid, and ferric chloride hexahydrate was dissolved in 1M methanesulfonic acid aqueous solution at 18wt% to obtain an oxidant solution; the oxidant solution was added dropwise to the mixed suspension at 3℃, and after the addition was completed, the mixture was ultrasonically treated at 27℃ at 100W for 6h, filtered, washed with deionized water and ethanol, and dried to obtain cerium oxide-copolymer polypyrrole core-shell nanospheres; (3) Pyrrole and pyrrole-3-carboxylic acid were mixed in a molar ratio of 1:0.9 to obtain a mixed monomer; 1.25 times the total molar amount of ferric chloride hexahydrate was weighed, and ferric chloride hexahydrate was dissolved in anhydrous acetonitrile at 18 wt% to obtain oxidant solution 2; the mixed monomer was dissolved in anhydrous acetonitrile at 15 wt%, and oxidant solution 2 was added dropwise at 3℃. After the addition was completed, the reaction was continued for 18 h. The precipitate was collected in ice water, washed with anhydrous acetonitrile and deionized water, and dried to obtain copolymer polypyrrole. (4) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 2wt% to obtain a crosslinking agent solution; mix cerium oxide-copolymerized polypyrrole core-shell nanospheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.25:2.2 and grind for 17 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 80℃ for 2 h, and vacuum dry at 60℃ for 9 h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 27℃ for 6 min, take it out and rinse with methanol and deionized water, and vacuum dry at 60℃ for 12 h to obtain a polymer composite capacitor electrode material.

[0027] Comparative Example 3: A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:77:1.1:2.8:165. Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 10 min. Add cerium nitrate hexahydrate and continue to react for 20 min. Add hydrogen peroxide and continue to react for 30 min to obtain a mixed solution. Heat the mixed solution to 100℃ and keep it for 2 h. Transfer it to a high-pressure reactor and keep it at 180℃ for 17 h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid, and deionized water were mixed in a mass ratio of 1:2.4:4:125 and ultrasonically treated at 200W for 30 min to obtain a mixed suspension. Ferric chloride hexahydrate was weighed in a mass ratio of 1.25 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid. Ferric chloride hexahydrate was dissolved in 1M methanesulfonic acid aqueous solution at 18wt% to obtain an oxidizing agent solution. The oxidizing agent solution was added dropwise to the mixed suspension at 3℃. After the addition was complete, the mixture was ultrasonically treated at 27℃ at 100W for 6 h. The mixture was then filtered, washed with deionized water and ethanol, and dried to obtain the oxidizing agent. Cerium-copolymerized polypyrrole core-shell nanospheres: Cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate were weighed at a mass ratio of 1:0.76. The cerium oxide-copolymerized polypyrrole core-shell nanospheres were added to deionized water at 1 wt%, and the mixture was sonicated at 200 W for 30 min to obtain a suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres. The suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres was stirred at 67 °C for 8 min, and 1.5 wt% potassium permanganate aqueous solution was added dropwise. After the addition was completed, the reaction was continued for 2 h. The mixture was centrifuged, washed with deionized water and anhydrous ethanol, and freeze-dried to prepare fractionated porous core-shell microspheres. (3) Weigh 1.25 times the molar amount of pyrrole, dissolve 18 wt% of ferric chloride hexahydrate in anhydrous acetonitrile to obtain oxidant solution 2; dissolve pyrrole in anhydrous acetonitrile at 15 wt%, add oxidant solution 2 dropwise at 3℃, continue the reaction for 18 h after the addition is complete, precipitate in ice water, wash with anhydrous acetonitrile and deionized water, dry, and obtain polypyrrole; (4) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 2wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.25:2.2 and grind for 17 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 80℃ for 2 h, and vacuum dry at 60℃ for 9 h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 27℃ for 6 min, take it out and rinse with methanol and deionized water, and vacuum dry at 60℃ for 12 h to obtain a polymer composite capacitor electrode material.

[0028] Comparative Example 4: A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:77:1.1:2.8:165. Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 10 min. Add cerium nitrate hexahydrate and continue to react for 20 min. Add hydrogen peroxide and continue to react for 30 min to obtain a mixed solution. Heat the mixed solution to 100℃ and keep it for 2 h. Transfer it to a high-pressure reactor and keep it at 180℃ for 17 h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid, and deionized water were mixed in a mass ratio of 1:2.4:4:125 and ultrasonically treated at 200W for 30 min to obtain a mixed suspension. Ferric chloride hexahydrate was weighed in a mass ratio of 1.25 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid. Ferric chloride hexahydrate was dissolved in 1M methanesulfonic acid aqueous solution at 18wt% to obtain an oxidizing agent solution. The oxidizing agent solution was added dropwise to the mixed suspension at 3℃. After the addition was complete, the mixture was ultrasonically treated at 27℃ at 100W for 6 h. The mixture was then filtered, washed with deionized water and ethanol, and dried to obtain the oxidizing agent. Cerium-copolymerized polypyrrole core-shell nanospheres: Cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate were weighed at a mass ratio of 1:0.76. The cerium oxide-copolymerized polypyrrole core-shell nanospheres were added to deionized water at 1 wt%, and the mixture was sonicated at 200 W for 30 min to obtain a suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres. The suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres was stirred at 67 °C for 8 min, and 1.5 wt% potassium permanganate aqueous solution was added dropwise. After the addition was completed, the reaction was continued for 2 h. The mixture was centrifuged, washed with deionized water and anhydrous ethanol, and freeze-dried to prepare fractionated porous core-shell microspheres. (3) Pyrrole and pyrrole-3-carboxylic acid were mixed in a molar ratio of 1:0.9 to obtain a mixed monomer; 1.25 times the total molar amount of ferric chloride hexahydrate was weighed, and ferric chloride hexahydrate was dissolved in anhydrous acetonitrile at 18 wt% to obtain oxidant solution 2; the mixed monomer was dissolved in anhydrous acetonitrile at 15 wt%, and oxidant solution 2 was added dropwise at 3℃. After the addition was completed, the reaction was continued for 18 h. The precipitate was collected in ice water, washed with anhydrous acetonitrile and deionized water, and dried to obtain copolymer polypyrrole. (4) Dissolve 1,4-dibromobutane in methanol at 2wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.25:2.2 and grind for 17 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 80℃ for 2 h, and vacuum dry at 60℃ for 9 h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 27℃ for 6 min, take it out and rinse with methanol and deionized water, and vacuum dry at 60℃ for 12 h to obtain a polymer composite capacitor electrode material.

[0029] Comparative Example 5: A method for preparing a polymer composite capacitor electrode material includes the following preparation steps: (1) Weigh out urea, cetyltrimethylammonium bromide (CTAB), deionized water, isopropanol, cyclohexane, and tetraethyl orthosilicate in a mass ratio of 1:1.67:50:0.83:12.5:2.5. Dissolve urea and CTAB in deionized water, add isopropanol and cyclohexane, sonicate at 100W for 20 min, add tetraethyl orthosilicate dropwise under sonication, and after the addition is complete, reflux at 70℃ for 16 h, centrifuge, wash with deionized water, and obtain oxidized urea. Silica microspheres were prepared by dispersing silica microspheres at 5 wt% in ethanol, sonicating at 100 W for 5 min, reacting at 78 °C for 3 h, washing with ethanol, centrifuging, and drying to obtain mesoporous silica microspheres. Mesoporous silica microspheres, pyrrole, pyrrole-3-carboxylic acid, ammonium persulfate, and deionized water were weighed at a mass ratio of 1:1:1:1:200. The mesoporous silica microspheres were dispersed in deionized water, and pyrrole and pyrrole-3-carboxylic acid were added dropwise at 27 °C. After the addition was complete, the mixture was sonicated at 100 W. After 1 hour of treatment, a mixed solution was obtained. At 27°C, 5 wt% ammonium persulfate aqueous solution was added dropwise to the mixed solution. The mixture was placed in a high-pressure reactor and reacted at 140°C for 8 hours. After centrifugation, the mixture was washed with deionized water and ethanol to obtain a silica / copolymerized polypyrrole composite. The silica / copolymerized polypyrrole composite was dispersed at 2 wt% in a 2M sodium carbonate aqueous solution and reacted at 60°C for 30 hours. After freeze-drying, hollow polypyrrole microspheres were obtained. Hollow polypyrrole microspheres were weighed at a mass ratio of 1:0.76. Hollow polypyrrole microspheres and potassium permanganate were weighed at a mass ratio of 1:0.76. The hollow polypyrrole microspheres were added to deionized water at a concentration of 1 wt%, and the mixture was sonicated at 200 W for 30 min to obtain a hollow polypyrrole microsphere suspension. The hollow polypyrrole microsphere suspension was stirred at 67 °C for 8 min, and 1.5 wt% potassium permanganate aqueous solution was added dropwise. After the addition was complete, the reaction was continued for 2 h. The mixture was then centrifuged, washed with deionized water and anhydrous ethanol, and freeze-dried to prepare fractionated porous core-shell microspheres. (2) Pyrrole and pyrrole-3-carboxylic acid were mixed in a molar ratio of 1:0.9 to obtain a mixed monomer; 1.25 times the total molar amount of ferric chloride hexahydrate was weighed, and ferric chloride hexahydrate was dissolved in anhydrous acetonitrile at 18 wt% to obtain oxidant solution 2; the mixed monomer was dissolved in anhydrous acetonitrile at 15 wt%, and oxidant solution 2 was added dropwise at 3℃. After the addition was completed, the reaction was continued for 18 h. The precipitate was collected in ice water, washed with anhydrous acetonitrile and deionized water, and dried to obtain copolymer polypyrrole. (3) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 2wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:0.25:2.2 and grind for 17 min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 80℃ for 2 h, and vacuum dry at 60℃ for 9 h to obtain polymer composite capacitor electrode material.

[0030] Experimental Example 1: Testing of electrode specific capacitance, cycle stability, and UV aging resistance. Specific capacitance testing and calculation method: Specific capacitance was calculated through constant current charge-discharge testing. A three-electrode system was used, and constant current charge-discharge testing was performed in a 3M potassium hydroxide aqueous solution using a CHI660E electrochemical workstation. The polymer composite capacitor electrode materials obtained in each embodiment and the materials of Comparative Examples 1-5 were cut into 1cm pieces. 2 A square electrode was used as the working electrode, a saturated glycerol electrode as the reference electrode, and a platinum wire as the counter electrode. The current density was 1 A / g. specific capacitance (F / g) = (I×∆t) / (M×∆V) Where I is the charge / discharge current (A), ∆t is the discharge time (s), M is the mass of the electrode active material (g), and ∆V is the voltage window (V).

[0031] Cyclic stability test method: The polymer composite capacitor electrode materials obtained in each embodiment and the materials of comparative examples 1 to 5 were subjected to 10,000 cycles using a constant current charge-discharge test. The stability of the electrode materials was examined by the ratio of the discharge specific capacitance of the last and first constant current charge-discharge tests.

[0032] UV aging resistance test: Referring to GB / T16422.3, the polymer composite capacitor electrode materials obtained in each example and the materials of comparative examples 1 to 5 were placed in an aging chamber equipped with UVA-340 lamps and continuously irradiated for 72 hours before being taken out and the mass specific capacitance was tested.

[0033] The results are shown in Table 1.

[0034] Table 1

[0035] The data in the table above verify that the electrode material formulation and preparation process of the embodiments of the present invention are superior to those of the comparative examples. Among Examples 1 to 3, Example 2 shows the best overall performance.

[0036] A comparison of Examples 1-3 and Comparative Example 1 reveals that the hollow cerium oxide nanostructure significantly improves the specific capacitance of the electrode material due to its unique thin-walled hollow morphology. The large inner surface of the hollow cerium oxide nanostructure serves as an effective active interface, greatly increasing the contact area between the electrode and the electrolyte, and providing pseudocapacitive active sites far exceeding those of solid particles. Simultaneously, its nanoscale thin shell drastically shortens the plasma phase diffusion distance, optimizing charge transport kinetics, thereby significantly improving the specific capacitance of the electrode material.

[0037] A comparison of Examples 1-3 and Comparative Example 2 reveals that potassium permanganate oxidation treatment enhances the specific capacitance of the material by constructing a manganese oxide nanoflower composite heterostructure and hierarchical channels. This is because the in-situ generated manganese oxide nanoflowers, acting as highly active pseudocapacitive materials, synergistically contribute additional Faraday capacitance to the polypyrrole shell, thereby significantly increasing the total specific capacitance of the electrode. Simultaneously, the growth process of the nanoflowers introduces abundant mesopores onto the material surface, forming a interconnected hierarchical pore network with the original structure. This greatly optimizes ion transport efficiency and the utilization rate of active sites, thus significantly improving the mass specific capacitance of the electrode material.

[0038] A comparison of Examples 1-3 and Comparative Example 3 reveals that the copolymerization strategy significantly optimizes charge transport at the electrode interface by introducing carboxyl functional groups, thereby improving the specific capacitance of the material. The carboxyl groups on the copolymer chain endow it with excellent hydrophilicity, greatly improving the wettability of the binder phase with the aqueous electrolyte and reducing the interfacial resistance to ion diffusion to the surface of the active material, thus improving the mass specific capacitance of the electrode material.

[0039] A comparison of Examples 1-3 and Comparative Example 4 reveals that the crosslinked network containing dynamic disulfide bonds significantly improves the cycling stability of the electrode while maintaining a high specific capacitance, compared to the crosslinked network containing only static alkyl chains. During long-term charge-discharge cycles, the reversible breaking and recombination capabilities of the dynamic disulfide bonds effectively dissipate the mechanical stress generated by changes in the volume of the active material, thus enabling the crosslinked network to be adaptive and maintain structural integrity. Simultaneously, the intermediate sulfur radicals generated during their breakage can participate in or modulate interfacial charge transport, playing a positive role in electron and ion conduction. Therefore, the use of 1,2-di(2-bromoethyl)disulfide imparts a superior long-term cycle life to the electrode material.

[0040] A comparison of Examples 1-3 and Comparative Example 5 reveals that the hollow cerium oxide structure significantly improves the specific capacitance of the material and provides a certain degree of resistance to UV aging. Cerium oxide itself is an excellent pseudocapacitive material; its hollow structure provides a high specific surface area, directly contributing a considerable Faraday capacitance. Its rigid framework also provides stable support for the outer polypyrrole and manganese oxide layers, which helps maintain the structural integrity of the electrode during long-term cycling. More importantly, as a highly efficient UV absorber and free radical quencher, cerium oxide can protect the photosensitive polypyrrole polymer chains and manganese oxide active material from the inside, effectively delaying their chemical degradation under light exposure, thereby ensuring the long-term service stability of the electrode in application environments that may face light exposure.

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended technical solutions rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of the equivalents of the claims be included within the present invention.

Claims

1. A polymer composite capacitor electrode material, characterized in that, The polymer composite capacitor electrode material is prepared by coating a mixture of hierarchical porous core-shell microspheres and copolymerized polypyrrole onto pretreated carbon cloth and then crosslinking it.

2. The polymer composite capacitor electrode material according to claim 1, characterized in that, The hierarchical porous core-shell microspheres are prepared by polymerizing hollow cerium oxide nanoparticles with pyrrole and pyrrole-3-carboxylic acid to obtain cerium oxide-copolymer polypyrrole core-shell nanospheres, which are then reacted with potassium permanganate.

3. The polymer composite capacitor electrode material according to claim 1, characterized in that, The copolymer polypyrrole is prepared by copolymerizing pyrrole and pyrrole-3-carboxylic acid in anhydrous acetonitrile with ferric chloride hexahydrate as an oxidant.

4. The polymer composite capacitor electrode material according to claim 1, characterized in that, The crosslinking is achieved by impregnating the coated electrode with a methanol solution of 1,2-bis(2-bromoethyl)disulfide.

5. A method for preparing a polymer composite capacitor electrode material, characterized in that, The preparation steps include the following: (1) Weigh urea, 10mM trisodium citrate aqueous solution, cerium nitrate hexahydrate, 30% hydrogen peroxide and deionized water according to the mass ratio 1:(75~79):(1~1.2):(2.5~3):(160~170). Dissolve urea in deionized water, add 10mM trisodium citrate aqueous solution and react for 5~15 min. Add cerium nitrate hexahydrate and continue to react for 15~25 min. Add hydrogen peroxide and continue to react for 20~40 min to obtain a mixed solution. Heat the mixed solution to 95~105℃ and maintain for 1.5~2.5 h. Transfer to a high-pressure reactor and maintain at 175~185℃ for 15~20 h. Centrifuge, wash with deionized water, and dry to obtain hollow nano-cerium oxide. (2) Hollow nano-cerium oxide, pyrrole, pyrrole-3-carboxylic acid and deionized water are mixed at a mass ratio of 1:(2.3~2.5):(3.9~4.1):(120~130) and ultrasonically treated at 100~300W for 25~35min to obtain a mixed suspension; 1.2~1.3 times the total molar amount of pyrrole and pyrrole-3-carboxylic acid ferric chloride hexahydrate is weighed and dissolved in 1M methanesulfonic acid aqueous solution at 16wt%~20wt% to obtain an oxidizing agent solution; the oxidizing agent solution is added dropwise to the mixed suspension at 0~5℃. After the addition is complete, the mixture is ultrasonically treated at 25~30℃ at 80~120W for 5~7h, filtered, washed with deionized water and ethanol, and dried. Cerium oxide-copolymerized polypyrrole core-shell nanospheres were prepared. Cerium oxide-copolymerized polypyrrole core-shell nanospheres and potassium permanganate were weighed at a mass ratio of 1:(0.7~0.8). The cerium oxide-copolymerized polypyrrole core-shell nanospheres were added to deionized water at a concentration of 0.5wt%~1.5wt%, and the mixture was ultrasonically treated at 100~300W for 25~35min to obtain a suspension of cerium oxide-copolymerized polypyrrole core-shell nanospheres. The suspension was stirred at 65~70℃ for 5~10min, and 1wt%~2wt% potassium permanganate aqueous solution was added dropwise. After the addition was complete, the reaction continued for 1.5~2.5h. The mixture was centrifuged, washed with deionized water and anhydrous ethanol, and freeze-dried to obtain fractionated porous core-shell microspheres. (3) Mix pyrrole and pyrrole-3-carboxylic acid at a molar ratio of 1:(0.8~1) to obtain a mixed monomer; weigh 1.2~1.3 times the total molar amount of ferric chloride hexahydrate, dissolve ferric chloride hexahydrate in anhydrous acetonitrile at 16wt%~20wt% to obtain oxidant solution 2; dissolve the mixed monomer in anhydrous acetonitrile at 10wt%~20wt%, add oxidant solution 2 dropwise at 0~5℃, and continue the reaction for 12~24h after the addition is complete, precipitate in ice water, wash with anhydrous acetonitrile and deionized water, dry, and obtain copolymer polypyrrole; (4) Dissolve 1,2-di(2-bromoethyl)disulfide in methanol at 1wt%~3wt% to obtain a crosslinking agent solution; mix hierarchical porous core-shell microspheres, copolymerized polypyrrole and N-methylpyrrolidone at a mass ratio of 1:(0.23~0.27):(1.9~2.4), grind for 15~20min to obtain a uniform slurry; coat the uniform slurry onto pretreated carbon cloth, dry at 70~90℃ for 1~3h, and vacuum dry at 55~65℃ for 8~10h to obtain an intermediate electrode; immerse the intermediate electrode in the crosslinking agent solution, react at 25~30℃ for 5~7min, take it out and rinse with methanol and deionized water, and vacuum dry at 55~65℃ for 11~13h to obtain a polymer composite capacitor electrode material.

6. The method for preparing a polymer composite capacitor electrode material according to claim 5, characterized in that, The hollow cerium oxide nanoparticles described in step (1) have an average diameter of 324±32nm and a wall thickness of 62±8nm.

7. The method for preparing a polymer composite capacitor electrode material according to claim 5, characterized in that, The pretreatment method for the carbon cloth in step (4) is as follows: 65% nitric acid and 95% sulfuric acid are mixed evenly at a volume ratio of 1:2 to obtain a mixed acid; potassium permanganate is dissolved in the mixed acid at a concentration of 4wt%~4.5wt% to obtain an oxidizing solution; the carbon cloth is immersed in the oxidizing solution and reacted at 25~35℃ for 5~7h; 3~4 times the volume of deionized water is added to the oxidizing solution and the reaction continues for 2.5~3.5h; 2~3 drops of 33% hydrogen peroxide solution are added and the reaction continues for 10~20min; the carbon cloth is removed, washed with deionized water and anhydrous ethanol, and dried to obtain the pretreated carbon cloth.

8. The method for preparing a polymer composite capacitor electrode material according to claim 7, characterized in that, The carbon cloth is model W0S1011.

9. The method for preparing a polymer composite capacitor electrode material according to claim 5, characterized in that, The reaction after immersion in the crosslinking agent solution in step (4) is as follows: 。